Be Fu**ing Perfect: À Procura da Perfeição - Pussetti, Chiara (Etnográfica Press, 2024)
This volume – which reports on the results of the research project EXCEL The Pursuit of Excellence, coordinated by the author at the Institute of Social Sciences of the University of Lisbon – presents ambitions, desires and practices of beautification and human improvement, discussing the dramas associated with the normativity of hegemonic ideals of beauty and perfection in contemporary society. This volume is driven by the hope that in the near future we will be able to make our ideals of beauty more inclusive and inclusive. So that each person can be who they are, in their specificity, occupying the space they want in the world, in freedom.